Blood dendritic cell levels associated with impaired IL‐12 production and T‐cell deficiency in patients with kidney disease: implications for post‐transplant viral infections. (20th August 2014) - Chen, Ping; Sun, Qianmei; Huang, Yanfei; Atta, Mohamed G.; Turban, Sharon; Segev, Dorry L.; Marr, Kieren A.; Naqvi, Fizza F.; Alachkar, Nada; Kraus, Edward S.; Womer, Karl L.
Summary Reduced pretransplant blood myeloid dendritic cell (mDC) levels are associated with post‐transplant BK viremia and cytomegalovirus (CMV) disease after kidney transplantation. To elucidate potential mechanisms by which mDC levels might influence these outcomes, we studied the association of mDC levels with mDC IL‐12 production and T‐cell level/function. Peripheral blood (PB) was studied in three groups: (i) end stage renal disease patients on hemodialysis (HD; n = 81); (ii) chronic kidney disease stage IV‐V patients presenting for kidney transplant evaluation or the day of transplantation (Eval/Tx; n = 323); and (iii) healthy controls (HC; n = 22). Along with a statistically significant reduction in mDC levels, reduced CD8+ T‐cell levels were also demonstrated in the kidney disease groups compared with HC. Reduced PB mDC and monocyte‐derived DC (MoDC) IL‐12 production was observed after in vitro LPS stimulation in the HD versus HC groups. Finally, ELISpot assays demonstrated less robust CD3+ INF‐γ responses by MoDCs pulsed with CMV pp65 peptide from HD patients compared with HC. PB mDC level deficiency in patients with kidney disease is associated with deficient IL‐12 production and T‐cell level/function, which may explain the known correlation of CD8+ T‐cell lymphopenia with deficient post‐transplant antiviral responses.